Condition of Drainage System and Its Impact on the Residents of Mowe, Ogun State, Nigeria - Ajayi, Ayodeji Olusola; Oladiran, Testimony Ayomide; Oyerinde, Ismail Adedapo; Ajayi, Aderonke Olufunmi; Fakanlu, Adonis Busuyi (CSID Journal of Infrastructure Development, 2024)
This study examines the impacts of drainage infrastructure conditions on Mowe, Ogun State, residents. The study used a quantitative research design, using a systematic random sampling technique to select ten (10) residential estates (three public-owned and seven privately owned) in the study area. In all, 107 residents were sampled using a structured questionnaire. The data collected was analysed using descriptive statistics. Based on the findings of this study, it was evident that the surface drainage system, mainly constructed with sandcrete blocks, was predominant in the study area. The result established that the drainage's minimum height in the study area was 0.1524 metres, while the maximum was 0.889 meters. The analysis shows that the effect of flooding was mostly on properties (68.6%). Moreover, the majority of the residents agreed that drainage infrastructure had an impact on their living conditions. The study underscores the need for policy implications that could aid in the formulation of relevant policies by the Department of Flood and Erosion Control in the Ogun State Ministry of Environment towards improving the residents' quality of life and the environment.